The implementation of critical thinking development strategies into technology education: The evidence from Slovakia - Brečka, Peter; Valentová, Monika; Lančarič, Drahoslav (Teaching and teacher education, 2022)
This research study examines the issue of the implementation of strategies for developing students’ critical thinking skills in technical subjects at primary and secondary vocational schools, with a focus on cognitive, interpersonal, technical, and communication skills. Multivariate significance tests identified several significant factors — personal and professional teacher characteristics and characteristics of a school (age, gender, length of teaching experience, education degree, work position, establisher, location, and stage of education) — that influence the implementation of developmental strategies. The study focuses on Slovakia, whose education system is typical of post-communist countries, so its results are applicable to other education systems with the same context. •The study focuses on factors affecting the implementation of the developmental strategies in a post-communist education system.•The study specifically examines the implementation of strategies for the development of critical thinking.•The implementation is influenced by a teacher's personal and professional characteristics.•It also differs depending on the characteristics of a school.•The findings are interesting for teachers, school managers, and educational policy makers.